Exact spherically-symmetric inhomogeneous model with n perfect fluids - Marra, Valerio; Pääkkönen, Mikko (Journal of cosmology and astroparticle physics, 2012)
We present the exact equations governing the dynamics of a spherically-symmetric inhomogeneous model with n decoupled and non-comoving perfect fluids. Thanks to the use of physically meaningful quantities we write the set of 3+2 n equations in a concise and transparent way. The n perfect fluids can have general equations of state, thus making the model extremely flexible to study a large variety of cosmological and astrophysical problems. As applications we consider a model sourced by two non-comoving dust components and a cosmological constant, and a model featuring dust and a dark energy component with negligible speed of sound.